Structure of NADP+‐bound 7β‐hydroxysteroid dehydrogenase reveals two cofactor‐binding modes. Issue 5 (1st May 2017) - Wang, Rui; Wu, Jiaquan; Jin, David Kin; Chen, Yali; Lv, Zhijia; Chen, Qian; Miao, Qiwei; Huo, Xiaoyu; Wang, Feng
Abstract : The structure of a binary complex of NADP + with 7β‐hydroxysteroid dehydrogenase reveals two modes of cofactor binding. Abstract : In mammals, bile acids/salts and their glycine and taurine conjugates are effectively recycled through enterohepatic circulation. 7β‐Hydroxysteroid dehydrogenases (7β‐HSDHs; EC 1.1.1.201), including that from the intestinal microbe Collinsella aerofaciens, catalyse the NADPH‐dependent reversible oxidation of secondary bile‐acid products to avoid potential toxicity. Here, the first structure of NADP + bound to dimeric 7β‐HSDH is presented. In one active site, NADP + adopts a conventional binding mode similar to that displayed in related enzyme structures. However, in the other active site a unique binding mode is observed in which the orientation of the nicotinamide is different. Since 7β‐HSDH has become an attractive target owing to the wide and important pharmaceutical use of its product ursodeoxycholic acid, this work provides a more detailed template to support rational protein engineering to improve the enzymatic activities of this useful biocatalyst, further improving the yield of ursodeoxycholic acid and its other applications.